La recaudación del impuesto iva y sus variaciones en los régimenes aplicados al periodo 2019-2020-2021 en la provincia de Cotopaxi - Galarza Tapia, Angélica Liliana (2023)
The analysis of the investigative project was developed using data obtained from the province of Cotopaxi, from the different taxpayers; The research problem was established in the variation of the collection of the Value Added Tax in the different regimes in force under the regulations and legal decrees in the period 2019 - 2021; The objective of this work is to carry out a study of the variability in the collection of this tax in the General Regime, Simplified Tax Regime (RISE) and the Microenterprise Regime, which were in force in the period under study.